Regeneration dynamics of woody vegetation in a Mediterranean landscape under different disturbance‐based management treatments. Issue 1 (19th October 2016) - Bashan, Danielle; Bar‐Massada, Avi
Abstract: Question: Mediterranean landscapes have been affected for millennia by agro‐pastoral disturbances such as grazing and vegetation clearing. Increased levels of fine‐scale habitat heterogeneity that resulted from these disturbances contribute to reduced wildfire risk and increased species diversity. Disturbance‐based management tools utilize disturbances in order to promote biodiversity and reduce fire risk, but are complicated to apply effectively due to the natural regeneration ability of many woody species following disturbances. Therefore, their successful application requires a better understanding of woody regeneration dynamics. Here, we asked how disturbance‐based management treatments affected the spatiotemporal dynamics of woody vegetation across 11 yrs in a Mediterranean landscape. Location: Ramat HaNadiv LTER, northern Israel. Methods: We analysed vegetation dynamics in a field experiment comprising five treatments: cattle grazing, goat grazing, shrub clearing, shrub clearing followed by goat grazing and undisturbed control. We used image analysis of high‐resolution aerial photographs to map woody patches in our study plots. We then quantified the spatial pattern of woody vegetation using multiple landscape indices, and conducted a comparative analysis of woody regeneration rates under different management treatments. Results: Cattle grazing did not inhibit woody regeneration, as regeneration rates were similar to those found in undisturbed control plots. Shrub clearing led to rapid woody regeneration (7 % yr −1 ), while a combination of shrub clearing and intense goat grazing halted woody regeneration completely. Finally, intense goat grazing not only prevented woody regeneration but led to significant decline in woody cover (1% yr −1 ). Conclusions: Our results highlight the rapid regenerative response of woody vegetation to severe disturbances, and the growth rates we found can serve as guidelines for long‐term management regimes aimed at maintaining low woody cover and biomass in fuel breaks and buffer zones. Abstract : Disturbance‐based management is commonly used to manipulate vegetation structure in Mediterranean landscapes, but its long‐term application is complex because many species are adapted to disturbances. We analyzed the long‐term dynamics of vegetation under multiple disturbances in a field experiment to reveal the effects of treatments on vegetation structure, and to estimate regeneration rates that can be used for management planning.